2020
DOI: 10.1017/s0033291720003785
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality exposure therapy for social anxiety disorder: a systematic review and meta-analysis

Abstract: Background Virtual reality exposure therapy (VRET) is currently being used to treat social anxiety disorder (SAD); however, VRET's magnitude of efficacy, duration of efficacy, and impact on treatment discontinuation are still unclear. Methods We conducted a meta-analysis of studies that investigated the efficacy of VRET for SAD. The search strategy and analysis method are registered at PROSPERO (#CRD42019121097). Inclusion criteria were: (1) studies that targeted patients with SAD or rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 57 publications
(58 reference statements)
3
41
0
4
Order By: Relevance
“…Regarding the combination of different treatment methods, although VRET is an effective method used in monotherapy (11)(12)(13)(14)(15)(16), however, it may be much more effective when combined with pharmacotherapy (30). When VRET is used with pharmacotherapy, the number of sessions can be shortened [e.g., 4 sessions in agoraphobia; (30)].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the combination of different treatment methods, although VRET is an effective method used in monotherapy (11)(12)(13)(14)(15)(16), however, it may be much more effective when combined with pharmacotherapy (30). When VRET is used with pharmacotherapy, the number of sessions can be shortened [e.g., 4 sessions in agoraphobia; (30)].…”
Section: Discussionmentioning
confidence: 99%
“…In the most recent meta-analysis of 22 clinical trials with 703 participants by Horigome et al the effectiveness of the use of VR in the treatment of social phobia was analyzed ( 13 ). The effectiveness of VR in treating social phobia was shown to be significant and sustained over a long observation period.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, virtual-reality exposure therapy (VRET) has become a popular digital intervention for various psychological disorders ( 13 , 14 ). A systematic review of 10 studies showed that VRET was as effective as in vivo exposure therapy post-intervention ( 15 ). Moreover, a meta-analysis found a large effect size favoring VRET for SAD over waitlist, but a small effect size favoring in vivo (i.e., face-to-face) exposure therapy with a therapist over VRET based on six studies ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…While much of this discussion can be applied to the growing research base (and practice) of virtual reality exposure therapy [4,5,128,129], the advent of algorithmic devices (e.g., smartphones), VEoT, and virtual humans, add new ethical issues given potential for extending the patient's cognitive and affective processes beyond the wetware of their brains. The idea of "extended mind" characterizes human cognizing as comprising complex feedforward and feedback loops among brain, body, and the external world.…”
Section: Discussionmentioning
confidence: 99%